Hydrolyzed polyacrylamide modified diatomite waste as a novel adsorbent for organic dye removal: Adsorption performance and mechanism studies. (1st January 2020) - Ma, Tian; Wu, Yunhai; Liu, Ningning; Wu, Yunying
Graphical abstract: The selected graph can not only express the preparation of HPAM-DW by modifying HPAM molecules onto the surface of DW, but also presented the adsorption process and mechanism of MB and RY, which showed the purposes of this work simultaneously. Highlights: Dye adsorption capacity onto hydrolyzed polyacrylamide modified diatomite waste was studied. Adsorption time, adsorbent dosage, pH and initial concentration had great influences on the adsorption results. Flocculation and physical absorption played a main role in the adsorption process. Abstract: Brewery diatomite waste (DW) was reused as a novel adsorbent via being modified by hydrolyzed polyacrylamide (HPAM). The adsorption of hydrolyzed polyacrylamide modified diatomite waste (HPAM-DW) for methylene blue (MB) and reactive yellow (RY) were severally studied and compared. The DW and HPAM-DW were characterized by various methods including Scanning Electron Microscopy (SEM), Energy Dispersive Spectroscopy (EDS), Fourier Transform Infrared Spectroscopy (FTIR) and X-ray diffraction (XRD) to analyze their physical and chemical properties before and after modification. The effects of four adsorption parameters (adsorption time, adsorbent dosage, pH and initial concentration) were also studied. The maximum adsorption capacity of HPAM-DW for MB (at pH 9.0) and RY (at pH 2.0) was 37.12 mg/g and 32.83 mg/g, respectively at 30 °C. Moreover, the adsorption data was fitted by Langmuir, Freundlich and Dubinin-Radushkevich (D-R) adsorption isothermal models, and as a result, Langmuir presents the best correspondence (R 2 MB = 0.974, R 2 RY = 0.991). Also, pseudo-first was more responsible than pseudo-second model in reflecting the mechanism of adsorption process (R 2 MB = 0.997, R 2 RY = 0.973). Compared with DW, the adsorption efficiency of organic dyes have improved due to the synergistic effect of HPAM and DW. From the investigation, the synthesized HPAM-DW was proved to act as a promising adsorbent to remove the dye waste in the industrial wastewater.